IN VITRO MICROPROPAGATION AND CALLUS INDUCTION OF LAWSONIA INERMIS L. FROM SHOOT TIPS - NAZRA PAIKER; KUNUL KANDIR (The Bioscan, 2011)
Different concentration of phytohormones affected Callus formation of Lawsonia inermis L. Explant of Lawsonia inermis was cultured in MS medium supplemented with different concentration of IAA, IBA, 2,4-D, NAA, KN, BAP. Medium supplemented with various phytohormones for organogenesis. Cultures were kept on 25±2º temperature and 16 hr photoperiod while callus was observed on different concentration of auxin or cytokinin alone or in combination. Most suitable medium for callus formation from shoot tips was that 2, 4 – D (2.5 mgL-1) + IAA (0.5 mgL-1).